2017
DOI: 10.1530/ec-17-0215
|View full text |Cite
|
Sign up to set email alerts
|

GATA transcription factors in testicular adrenal rest tumours

Abstract: Testicular adrenal rest tumours (TARTs) are benign adrenal-like testicular tumours that frequently occur in male patients with congenital adrenal hyperplasia. Recently, GATA transcription factors have been linked to the development of TARTs in mice. The aim of our study was to determine GATA expression in human TARTs and other steroidogenic tissues. We determined GATA expression in TARTs (n = 16), Leydig cell tumours (LCTs; n = 7), adrenal (foetal (n = 6) + adult (n = 10)) and testis (foetal (n = 13) + adult (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Compared to adult adrenal tissue, TART highly overexpressed testis-specific DEFB119, PRM2, and GATA4 ( Figure 3B). GATA4 expression in TART has been reported previously by our group (20). Previous studies proposed the expression of the testis-specific Luteinizing Hormone/Choriogonadotropin Receptor (LHCGR) in TART (16,21).…”
Section: Tart Express Both Adrenal-and Testis-specific Genesmentioning
confidence: 52%
See 1 more Smart Citation
“…Compared to adult adrenal tissue, TART highly overexpressed testis-specific DEFB119, PRM2, and GATA4 ( Figure 3B). GATA4 expression in TART has been reported previously by our group (20). Previous studies proposed the expression of the testis-specific Luteinizing Hormone/Choriogonadotropin Receptor (LHCGR) in TART (16,21).…”
Section: Tart Express Both Adrenal-and Testis-specific Genesmentioning
confidence: 52%
“…The identity and functional characteristics of TART are incompletely understood. Previous research focusing on the characterization of TART reported both adrenal-(26-28) and testis-specific (20,27) characteristics. However, these studies focused only on a subset of candidate markers.…”
Section: Discussionmentioning
confidence: 99%
“…GATA4 is well known for its central role in embryogenesis [7], and in myocardial differentiation and function [8]. Besides, this protein is thought to be necessary for testicular development [9]. Mutations in this gene have been associated with various diseases.…”
Section: Introductionmentioning
confidence: 99%
“…They also might have a multiple primordial origin from pluripotent cells in the original locations. 4 These rests might be present in 50% of newborns, but most of them become atrophic by the time they reach adulthood.…”
Section: Editorial Comment To Testicular Adrenal Rest Tumor Without Cmentioning
confidence: 99%
“…It is accepted that adrenal rests were due to mechanical separation and displacement of portions of cortical tissue during migration and descent of the sex glands in male embryonic development. They also might have a multiple primordial origin from pluripotent cells in the original locations . These rests might be present in 50% of newborns, but most of them become atrophic by the time they reach adulthood.…”
mentioning
confidence: 99%